Grip Strength and the Risk of Cognitive Decline and Dementia: A Systematic Review and Meta-Analysis of Longitudinal Cohort Studies - Cui, Mengzhao; Zhang, Siwen; Liu, Yujia; Gang, Xiaokun; Wang, Guixia (Frontiers in Aging Neuroscience, 2021)
Purpose: Loss of grip strength and cognitive impairment are prevalent in the elderly, and they may share the pathogenesis in common. Several original studies have investigated the association between them, but the results remained controversial. In this systematic review and meta-analysis, we aimed to quantitatively determine the relationship between baseline grip strength and the risk of cognitive impairment and provide evidence for clinical work. Methods: We performed a systematic review using PubMed, EMBASE, Cochrane, and Web of Science up to March 23, 2020, and focused on the association between baseline grip strength and onset of cognitive impairment. Next, we conducted a meta-analysis using a hazard ratio (HR) and 95% confidence interval (CI) as effect measures. Heterogeneity between the studies was examined using I2 and p-value. Sensitivity analyses and subgroup analyses were also performed, and publication bias was assessed by Begg's and Egger's tests. Results: Fifteen studies were included in this systematic review. After sensitivity analyses, poorer grip strength was associated with more risk of cognitive decline and dementia (HR = 1.99, 95%CI: 1.71–2.32; HR = 1.54, 95%CI: 1.32–1.79, respectively). Furthermore, subgroup analysis indicated that people with poorer strength had more risk of Alzheimer's disease (AD) and non-AD dementia (HR = 1.41, 95%CI: 1.09–1.81; HR = 1.45, 95%CI: 1.10–1.91, respectively). Conclusions: Lower grip strength is associated with more risk of onset of cognitive decline and dementia despite of subtype of dementia. We should be alert for the individuals with poor grip strength and identify cognitive dysfunction early.